Periodontitis as a risk factor for systemic disease: Are microparticles the missing link?. Issue 6 (June 2015) - Badran, Zahi; Struillou, Xavier; Verner, Christian; Clee, Thibaud; Rakic, Mia; Martinez, Maria C.; Soueidan, Assem
Abstract: Periodontitis is an oral inflammatory disease affecting the teeth supportive tissue. Its bacterial infectious etiology is well established. Periodontitis has been associated with increased prevalence of systemic diseases such as cardiovascular diseases, diabetes, rheumatoid arthritis, preeclampsia, preterm birth and inflammatory bowel disease. The rational of considering periodontitis as risk factor for systemic disease is the passage of inflammatory cytokines and/or bacteria in the bloodstream, thus affecting distant organs. Membrane microparticles are released by multiple cells in inflammatory environment. Recent data suggested the role of these microparticles in the pathogenic process of many systemic diseases, that can be also associated to periodontitis. We hypothesized that periodontitis could be a chronic reservoir of microparticles, hence elucidating partially the interaction with systemic diseases initiation or progression.